Penghitungan Peak Ground Acceleration (PGA) di Desa Kuta Menggunakan Persamaan Empiris pada Gempabumi 19 Agustus 1977 (Mw = 8.3) - Annisa Sadela Suhada; Ricko Kardoso; Muhammad Zuhdi; Syamsuddin (Prodi Fisika FKIP Unram, 2023)
The August 19, 1977 earthquake was one of the major earthquakes that ever occurred in the Nusa Tenggara area with an impact on the island of Lombok, one of which was in Kuta Village. The purpose of this research is to determine the empirical equation that is suitable for use in Kuta Village to calculate the Peak Ground Acceleration (PGA) value in the form of a distribution map. The PGA value can provide an overview of the damage to buildings caused by the earthquake. The PGA calculation uses several empirical equations of Donovan, M.C.Guirre, Esteva, and Oliviera. Earthquake data was obtained through data released from the USGS and the destructive earthquake catalog. The PGA value obtained with the Donovan empirical equation is a PGA value that is close to the value from the results of the BMKG Shakemap scenario with the MMI III scale. This earthquake did not cause damage to the Kuta Village area but damage was caused by the tsunami after the earthquake occurred. Keywords: Sumba Earthquake, Kuta Village, Maximum Ground Acceleration, Empirical Equation.